Rule-based automated design check for modular building - Sun, Yanhui; Wu, Jeremy; Fan, Jingyuan; Wang, Jun; Wang, Xiangyu (2019)
Unlike conventional buildings, modular buildings require more time in design and planning but less time in execution. Lacking of experience and knowledge of downstream processes, underlying design issues become a critical barrier hindering the application of modular buildings. This paper contributes in developing a rule-based automated design check system for modular buildings harnessing the concept of design for manufacture, transportation, and assembly (DfMTA).The rule-based design check system includes DfMTA, Building Information Modelling (BIM), and Rule-based Engine three main parts that can facilitate entire modular construction process, in terms of design, manufacturing, transportation and assembly.